2020
DOI: 10.3390/biomedicines8090328
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Induces a Dual Response in Liver Function Tests: Association with Mortality during Hospitalization

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with abnormal liver function tests. We hypothesized that early altered liver biochemistries at admission might have different clinical relevance than subsequent changes during hospitalization. A single-center retrospective study was conducted on 540 consecutive hospitalized patients, PCR-diagnosed with SARS-CoV-2. Liver test abnormalities were defined as the elevation of either gamma-glutamyltransferase (GGT), alanine aminotransferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 40 publications
(51 reference statements)
1
41
0
4
Order By: Relevance
“…The authors concluded that SARS‐CoV‐2 may have a dual effect on the liver, characterized by elevated aminotransferases on admission followed by a marked cholestasis in patients with a fatal outcome (Figure 1). Median albumin levels were already lower on admission in non‐survivors than in survivors (3 g/dL vs 3.4 g/dL, respectively, P < .001), and further decreased in these patients during hospitalization 9 . In conclusion, abnormal liver function tests are common in COVID‐19, mainly in the form of transient increases in aminotransferases.…”
Section: Abnormal Liver Function Tests As Risk Factor For Severe Covid‐19mentioning
confidence: 76%
See 1 more Smart Citation
“…The authors concluded that SARS‐CoV‐2 may have a dual effect on the liver, characterized by elevated aminotransferases on admission followed by a marked cholestasis in patients with a fatal outcome (Figure 1). Median albumin levels were already lower on admission in non‐survivors than in survivors (3 g/dL vs 3.4 g/dL, respectively, P < .001), and further decreased in these patients during hospitalization 9 . In conclusion, abnormal liver function tests are common in COVID‐19, mainly in the form of transient increases in aminotransferases.…”
Section: Abnormal Liver Function Tests As Risk Factor For Severe Covid‐19mentioning
confidence: 76%
“…There was a negative correlation between initial oxygen saturation and ASAT but not GGT ( P <.001 and P =.944 respectively). A longitudinal analysis showed that the progression of GGT levels was positively correlated with inflammatory markers such as C‐reactive protein (CRP) and strongly increased in non‐survivors but not in survivors during hospitalization ( P < .001) 9 . The authors concluded that SARS‐CoV‐2 may have a dual effect on the liver, characterized by elevated aminotransferases on admission followed by a marked cholestasis in patients with a fatal outcome (Figure 1).…”
Section: Abnormal Liver Function Tests As Risk Factor For Severe Covid‐19mentioning
confidence: 98%
“…Decreased levels of albumin and higher levels of AST were also associated with the mortality of COVID-19 patients [191]. However, abnormal liver function tests were not associated with survival in hospitalized COVID-19 patients [192] but with increased risk of ICU admission [193].…”
Section: Deranged Lfts In Covid Patients and Mortalitymentioning
confidence: 98%
“…While elevations of cholestatic liver enzymes [alkaline phosphatase (ALP) and gamma glutamyl transferase (γGT)] were initially considered rather rare, 4,22,23,46 recent systemic reviews highlight elevations of ALP and γGT in 6.1% and 21.1% of COVID‐19 patients respectively 35,45 . Moreover, a biphasic pattern with initial transaminase elevations followed by cholestatic liver enzymes has been reported, which could reflect SIRS‐induced cholestasis at the hepatocellular/canalicular level or more severe bile duct injury in the later stage of the disease 47 . Although COVID‐19‐associated liver injury has been reported to be mild, it may affect a significant proportion of patients, especially those with a more severe disease course.…”
Section: The Spectrum Of Liver Involvement In Covid‐19mentioning
confidence: 99%